Analysing actor based reactions to real estate features in fast-growing urban areas - Brano , Glumac; Ad den, Otter; Jos , Smeets; Wim , Schaefer (2008)

(untitled)
This paper provides new insights for analyzing relations between actors and factors within urban development areas. Additionally, it contributes to basic characteristics and importance of classified actors in an urban development process. A study was defined, as part of a PhD research project to identify actors based reactions for decision making concerning real estate features in an urban development area. It is based on the analysis and comparison of possible methodologies and techniques to investigate such actor’s involvement in urban development processes. As a result a technique selection choice is presented for analyzing such actors based reactions. Better understanding of their characteristics concerning actions and links between actors will clarify their goals and interests. This paper provides a) an initial input for modeling urban development process such as: multi-actor environment, factors influencing decisions of actors and b) bring better insights in a development process which engages previous components. Further on, used and promising methodologies will be discussed considering modeling a specific actor behavior with relevant factors.